A NARRATIVE VIEW OF POLIOMYELITIS ERADICATION IN THE DEMOCRATIC REPUBLIC OF CONGO: CHALLENGES AND PROSPECTS: Risk of re-emergence of poliomyelitis in the DRC: impact of heterogeneous vaccination coverage - Lambert, Mulakwa Morisho; Bamavu , Amisi Charles; Chirimwami , Muganda Serge (Student’s Journal of Health Research Africa, 2025)
Poliomyelitis remains a persistent threat in the Democratic Republic of the Congo (DRC), despite intensified immunization campaigns. The country continues to experience recurrent outbreaks of vaccine-derived type 2 poliovirus (cVDPV2), highlighting gaps in eradication efforts. This narrative review aims to analyze the main challenges to polio eradication in the DRC and explore potential strategies to address them. The persistence of cVDPV2 in the DRC is due to uneven coverage, logistical challenges, low community engagement, vaccine supply issues, and insecurity in certain regions. Despite significant progress, including the Mashako protocol to reach unvaccinated children and improved surveillance for acute flaccid paralysis, these barriers continue to hamper eradication efforts. Addressing these issues requires a multi-sectoral approach, including investment in infrastructure, improved vaccination practices, active community mobilization, and enhanced security measures for vaccination teams in conflict areas. Strengthening cold chain logistics and implementing targeted strategies to address vaccine hesitancy are also critical. A coordinated effort between the government, partner organizations, and local communities is essential for polio eradication in the DRC. Future research should focus on optimizing immunization strategies, strengthening surveillance systems, and evaluating innovative approaches to overcome logistical and security challenges in immunization campaigns.